2020
DOI: 10.1002/adem.201900532
|View full text |Cite
|
Sign up to set email alerts
|

Creep and Superplasticity: Evolution and Rationalization

Abstract: Detailed studies on the creep behavior of materials are of scientific and practical significance. From a scientific point of view, data obtained from such studies are critical to the characterization of creep behavior in terms of deformation mechanisms. From a practical point of view, information inferred from such studies is useful because of its relevance to many design considerations. Over the past several decades, much progress has been made in rationalizing the creep behavior of metals and solid‐solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 165 publications
0
4
0
Order By: Relevance
“…According to the constitutive equation for superplasticity, a decrease in grain size is essential to achieve superplasticity at a high-strain rate 4,5,9,10 . Besides, Grain Boundary Sliding (GBS), the predominant deformation mechanism found in superplastic behavior, is predominantly observed in materials with small grains and high-angle grain boundaries 11,12 . More importantly, retention of Ultra-Fine Grains (UFGs) or nanoscale grains without significant grain growth at elevated temperatures is essential to accommodate GBS and GBS-induced cavitation through diffusion or dislocation motion 11,13,14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the constitutive equation for superplasticity, a decrease in grain size is essential to achieve superplasticity at a high-strain rate 4,5,9,10 . Besides, Grain Boundary Sliding (GBS), the predominant deformation mechanism found in superplastic behavior, is predominantly observed in materials with small grains and high-angle grain boundaries 11,12 . More importantly, retention of Ultra-Fine Grains (UFGs) or nanoscale grains without significant grain growth at elevated temperatures is essential to accommodate GBS and GBS-induced cavitation through diffusion or dislocation motion 11,13,14 .…”
mentioning
confidence: 99%
“…Besides, Grain Boundary Sliding (GBS), the predominant deformation mechanism found in superplastic behavior, is predominantly observed in materials with small grains and high-angle grain boundaries 11,12 . More importantly, retention of Ultra-Fine Grains (UFGs) or nanoscale grains without significant grain growth at elevated temperatures is essential to accommodate GBS and GBS-induced cavitation through diffusion or dislocation motion 11,13,14 . The representative CoCrFeMnNi HEA with a single Face-Centered Cubic (FCC) structure exhibited a reasonable superplastic elongation of 570% at elevated temperature 15 .…”
mentioning
confidence: 99%
“…Poly( -caprolactone)/PHB copolymer: Poly( -caprolactone) (PCL) has a high degree of crystallinity, a slow rate of degradation, and significant viscoelastic and rheological properties. [45] It is often utilized for a biodegradable polymer plasticizer as a result of its linear structure. It has been found that due to the presence of the segment PCL, the fracture growth rate, ductility, and mechanical processability of the composite can be significantly improved, and overall strengthening and toughening can be achieved.…”
Section: Pha/polyester-based Biodegradable Copolymermentioning
confidence: 99%
“…Grain boundary sliding is the key superplastic deformation mechanism that accommodated by dislocation and diffusional creep, and grain rotation [1]- [5] . Thus, for a good superplastic properties fine-grained structure and movable high angle grain boundaries are required [6]- [10] . Grain refinement improves superplasticity, strain rates and elongations increase that favor formability [11]- [13] .…”
Section: Introductionmentioning
confidence: 99%